Problem-based Learning (PBL) effect to students' critical thinking in biology class - Sepriadi, Ilham; Lufri, Lufri; Syamsurizal, Syamsurizal (Universitas Negeri Padang, 2023)
The ability to think critically is an potential that have to be possessed at the moment. crucial questioning skills are the ability to are searching for and method records so that it may be concluded and communicated. Given the importance of essential thinking capabilities, it need to be developed within the gaining knowledge of technique. one of the mastering models that can be used to increase students' crucial questioning talents is trouble-primarily based getting to know. The cause of this research is to research numerous clinical articles related to the application of trouble-based totally mastering in the biology learning procedure to enhance college students' important questioning skills, and to prove the impact of the hassle-primarily based mastering model. This research was performed the usage of the literature study approach on 20 scientific articles in the ultimate 10 years. The articles have been analyzed to prove that the hassle-based totally gaining knowledge of version can enhance college students' essential wondering skills within the biology getting to know process.